Management Accounting Practices and Organizational Performance: Moderating Role of Environmental Contingencies of Listed Manufacturing Companies in Sri Lanka. - Achchi, M.I.J. (University of Jaffna, 2021)
Management accounting practices are important for collecting, classifying, computing, and communicating appropriate information in the process of making strategic decisions, thereby improving organizational performance. Sri Lankan manufacturing industry encounters global competition, environmental turbulence, and technological transformation, which challenge the achievement of its continuous performance. This research mainly investigates the impact of management accounting practices (MAPs) on the organizational performance of manufacturing companies listed under the Colombo Stock Exchange in Sri Lanka. The relationships between management accounting practices and organizational performance, the moderating effect of environmental contingencies on the relationship between management accounting practices and organizational performance, and differences of MAPs among different types of manufacturing sectors were also examined within this research. Drawing from the contingency theory of management accounting and extensive empirical review of literature, ten sets of MAPs and two contingency variables were employed to develop the conceptual framework. There were four main hypotheses and fifty-nine sub-hypotheses were developed to evaluate the developed conceptual framework. Data were collected from ninety-six manufacturing companies listed under the Colombo Stock Exchange in Sri Lanka. Data were analyzed using Partial Least Squared Structural Equation Modelling (PLS-SEM) with Smart-PLS version 3.2, correlation analysis, and ANOVA test using IBM Statistical Package for Social Science (SPSS) version 23.0. The analysis revealed that the MAPs such as costing system, budgeting, standard costing, resource utilization techniques, risk management, and strategic planning significantly impact the organizational performance of listed manufacturing companies in Sri Lanka. However, MAPs like short-term decision systems, long-term decision systems, capital budgeting, and value creation techniques did not impact organizational performance. Further, it was found that all ten groups of MAPs individually and collectively have a positive relationship with the organizational performance of Sri Lankan listed manufacturing companies. The findings of moderating effect revealed that the complexity of the production process moderates the relationship between MAPs and organizational performance. But, perceived environmental uncertainty did not support the moderating effect. Finally, a significant difference was found among manufacturing companies on value creation techniques, resource utilization techniques, and strategic planning. However, no significant difference was found among the different manufacturing sectors on costing system, short-term decision system, long-term decision system, budgeting, standard costing system, capital budgeting, and risk management.
Keywords: Management accounting practices; Organizational performance; Financial performance; Non-financial performance; Environmental contingencies